Нормування вимог щодо токсичної небезпеки продуктів горіння кабельної продукції - Шафран, Л.М.; Харченко, І.О.; Кравченко, Р.І.; Скоробагатько, Т.М.; Новак, С.В. (Актуальні проблеми транспортної медицини, 2007)
Получены зависимости для оценки токсичной опасности продуктов горения изолированных проводов и кабелей. Показано, что оценку токсичной опасности продуктов горения этих изделий, а также строительных конструкций целесообразно выполнять по отношению показателя токсичности продуктов горения к массовой скорости выгорания. На основании результатов исследований установлено, что для обеспечения пожарной безопасности людей на объектах целесообразно применять изолированные провода и кабели с показателем токсичности продуктов горения более 120 пм-3, что согласовывается с требованиями государственных строительных норм (ДБН) в области проектирования и строительства объектов гражданского назначения. The dependences for an estimation of toxic hazard fire effluents of insulated wires and cables have been obtained. It has been shown that it is possible to carry out estimation of toxic hazard fire effluents of these articles, and also of building constructions taking into account ratio of toxic index of fire effluents to their burn-up mass rate. On of results of studies it has been established that in order to provide of fire safety of persons within facilities it is expedient to apply insulated wires and cables with toxic index fire effluents above 120 g-m-3, that agrees with the requirements of state building norms (flBH) in the domain of designing and building of civil facilities.